Cathode and lithium ion battery with same
By covalently bonding the electrode binder on the surface of the cathode active material of the lithium-ion battery cathode, the problem of uneven components is solved, and the service life and electrochemical characteristics of the cathode are improved.
Patent Information
- Application Number
- CN202380049796.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-25
- Filing Date
- 2023-07-12
- Publication Date
- 2025-02-11
AI Technical Summary
The uneven distribution of the components of the cathode of existing lithium-ion batteries in the composite material affects its service life, reliability and electrochemical characteristics.
By directly covalently bonding the electrode binder to the surface of the cathode active material, surface functionalized cathode active material particles are formed, thereby reducing process steps and improving composition uniformity when preparing the coating composition.
The uniform distribution of cathode active materials, electrode binders and conductive additives in the composite material is achieved, which significantly improves the service life, reliability and high current load capacity of the cathode.
Abstract
Description
Technical Field
[0001] The invention relates to a cathode and a lithium ion battery having the cathode. Background Art
[0002] In the following, the term "lithium-ion battery" is used synonymously with all names commonly used in the prior art for lithium-containing galvanic elements and cells, such as lithium cells, lithium-ion cells, lithium polymer cells and lithium-ion accumulators. In particular, rechargeable batteries (secondary batteries) are included. The terms "battery" and "electrochemical cell" are also used synonymously with the term "lithium-ion battery".
[0003] Lithium-ion batteries include a positive electrode (cathode) and a negative electrode (anode). The cathode has a cathode active material that can reversibly absorb or release lithium ions. In order to support the absorption and release of lithium ions in the cathode active material and to further improve the properties of the assembled cathode, additives such as electrode binders and conductive additives such as carbon black and optional dispersants are usually mixed into the composite cathode. The cathode active material and the additive are present together in a composite material, that is, in a mixture applied to a cathode current collector made of aluminum. Such a cathode is also referred to as a composite cathode in the prior art.
[0004] The composition of the cathode is an important aspect of the cell chemistry of lithium-ion batteries. In particular, certain electrochemical properties of lithium-ion batteries (such as high current carrying capacity or cycle stability, service life) can be decisively adjusted through the selection and composition of the composite material.
[0005] In order to prepare this composite electrode, first a coating composition (cathode slurry) must be prepared. The coating composition comprises a uniform mixture formed by a cathode active material, an electrode binder, a conductive additive, optional other additives and a carrier solvent. This coating composition is applied to the cathode current collector and dried. During the drying process, the carrier solvent (e.g., NMP or water) present is removed, and a composite material is formed on the surface of the current collector.
[0006] In order to improve the electrochemical properties of the cathode and thus also the electrochemical properties of the lithium ion battery, and to achieve a certain high current load capacity and cycle stability, it is desirable to achieve a uniform distribution of the individual components in the composite material. However, there are many aspects that hinder the uniform distribution of the individual components in the composite material, for example, the use of an uneven coating composition to produce the composite material, or inappropriate drying conditions during the drying of the coating composition. The uneven distribution of the components in the composite material can adversely affect the service life, reliability and electrochemical properties of the cathode, and therefore can also adversely affect the lithium ion battery prepared therefrom. Summary of the invention
[0007] It is therefore an object of the present invention to provide a cathode which can be produced simply and cost-effectively and which satisfies the electrochemical performance requirements imposed on the use in lithium-ion batteries.
[0008] According to the invention, this object is achieved by a cathode for a lithium-ion battery according to claim 1 .
[0009] Advantageous embodiments of the cathode according to the invention are specified in the dependent claims, which can be selectively combined with one another.
[0010] According to the invention, this object is achieved by a cathode for a lithium ion battery, wherein the cathode comprises the following components:
[0011] (A) at least one cathode active material; and
[0012] (B) at least one electrode binder;
[0013] The cathode active material of component (A) is present in the form of particles, and at least a portion of the electrode binder of component (B) is covalently bonded to the surface of the particles.
[0014] The present invention is based on the following basic concept, that is, the electrode binder is directly chemically connected with the cathode active material, so that the electrode binder is fixed on the surface of the cathode active material. In other words, the particles of the cathode active material are surface functionalized by the electrode binder.
[0015] Furthermore, advantageously, when preparing the coating composition, it is no longer necessary to prepare a separate electrode binder solution as was common before and to mix it with the cathode active material and, if necessary, intensively with carbon black; instead, the cathode active material can be functionalized with the electrode binder in advance and stored as a surface-functionalized cathode active material powder. Then, when preparing the coating composition, the powder with the surface-functionalized cathode active material particles can be weighed together with other additives in only one single step and then suspended together in a solvent. In this way, the process steps required for the slurry preparation can be reduced, thereby accelerating and simplifying the preparation process as a whole. Therefore, time and resources are saved during the preparation, and the cathode itself is also more cost-effective.
[0016] In addition, the homogeneity of the composite material is also improved, since the electrode binder and the cathode active material are already present as a homogeneous unit. As a result, the service life, reliability and high current carrying capacity of the cathode can be significantly improved.
[0017] According to the present invention, the cathode comprises at least one cathode active material as component (A). The cathode active material of component (A) is not limited in principle, and any cathode active material known in the prior art that can form a cathode for a lithium ion battery can be used.
[0018] Suitable cathode active materials for the cathode may therefore be all cathode active materials known in the prior art that are capable of reversibly absorbing or releasing lithium ions. In particular, cathode active materials as disclosed in the scientific article by D. Andre et al. (J. Mater. Chem. A, 2015, 3, 6709-6732) may be used. [1]
[0019] According to a first aspect, the cathode active material is selected from lithium cobalt oxide (LCO), lithium nickel oxide (LNO), lithium nickel cobalt aluminum oxide (NCA), lithium nickel manganese cobalt oxide (NMC), lithium nickel manganese oxide (NMx), lithium-rich and manganese-rich lithium nickel manganese cobalt oxide or lithium nickel manganese oxide (LMR), lithium manganese oxide (LMO), lithium iron phosphate (LFP), lithium manganese iron phosphate (LMFP), spinel lithium nickel manganese oxide (LNMO) and their derivatives and combinations.
[0020] Lithium nickel manganese cobalt oxide compounds are also known by the abbreviation NMC, occasionally also alternatively by the technical abbreviation NCM. NMC-based cathode active materials are used in particular for lithium-ion batteries for electric vehicles. NMC as cathode active material has an advantageous combination of desired properties, such as high specific capacity, reduced cobalt content, high current carrying capacity and high intrinsic safety, which, for example, exhibits sufficient stability in the event of overcharging.
[0021] NMC can be used with the general unit Li α Ni x Mn y Co z O 2 Description, where x+y+z=1, where α represents the stoichiometric ratio of lithium, usually between 0.8 and 1.15. The specific stoichiometric ratio is given in the literature as a three-digit number, such as NMC-811, NMC-622, NMC-532 and NMC-111. These three digits give the relative content of nickel: manganese: cobalt respectively. In other words: For example, NMC-811 is a general unit of LiNi 0.8 Mn 0.1 Co 0.1 O 2 In addition, the cathode active material with the general formula unit Li 1+E (Ni x Mn y Co z ) 1-E O 2The above-mentioned lithium-rich and manganese-rich NMC, wherein E is in particular between 0.1 and 0.6, preferably between 0.2 and 0.4. Silicon-rich layered oxides are also referred to as overlithiated (layered) oxides (OLO).
[0022] As mentioned above, the cathode active material is present in the form of particles, and the electrode binder (B) is covalently bonded to the surface of the particles. The particles of the cathode active material can have a particle size distribution with an average particle diameter in the range of 0.01 μm to 30 μm, preferably in the range of 50 nm to 1000 nm. The particle diameter can be determined using an electron micrograph (TEM, SEM) or by means of dynamic light scattering (DLS). Here, the average particle diameter is measured in the absence of an electrode binder.
[0023] In addition to at least one cathode active material, the cathode according to the invention also comprises at least one electrode binder of component (B) which is at least partially covalently bonded to the surface of the cathode active material.
[0024] Electrode binders are understood below to be fillers with adhesion-promoting properties, so that the filler holds the remaining components of the cathode together. In this regard, the electrode binder of component (B) is not restricted, and in principle any electrode binder from the prior art that can function as an electrode binder in a cathode of a lithium ion battery can be used.
[0025] The electrode binder can be a polymer, for example, a non-fluorinated polymer selected from hydrogenated acrylonitrile-butadiene rubber (HNBR), carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyacrylate (PAA), polyvinyl alcohol (PVA), polyvinyl pyrrolidone (PVP), and combinations thereof.
[0026] Alternatively, the electrode binder may be a fluorine-containing polymer having a basic backbone G. In principle, the basic backbone G may comprise an aliphatic at least partially fluorinated hydrocarbon backbone, which may be linear, cyclic or branched.
[0027] In one embodiment, the basic backbone G of the fluoropolymer is at least partially fluorinated and has a structure selected from vinylidene fluoride (—CH 2 CF 2 -) and hexafluoropropylene (-CF 2 CF(CF 3 )-) repeating unit. Combinations of the above units are also contemplated. It can also be tetrafluoroethylene (-CF 2 -CF 2 -) unit. PTFE electrode binders themselves are known, for example, from US 2013 157 141 A1.
[0028] The fluorinated polymer having the basic skeleton G may have a molar mass M in the range of 100 to 2000 kDa, preferably 500 to 1500 kDa. w .
[0029] Fluorine-containing polymers having a basic skeleton G may have additional polar groups, for example maleic anhydride or free acid groups, in particular in PVdF. Such polar-modified PVdF electrode binders are known from EP 2 147 029 B1.
[0030] For example, the fluorine-containing polymer may be a polymer selected from polyvinylidene fluoride (PVDF) and poly(vinylidene fluoride-hexafluoropropylene) copolymer (PVDF-HFP).
[0031] For example, you can use The homopolymers or copolymers of the company as fluoropolymers, such as 5130(homopolymer), 21216(PVdF-HFP). You can also use The company's fluoropolymers, such as the KF polymer series, or Arkema's fluoropolymers, such as Polymer series.
[0032] The above-mentioned electrode binder has a high affinity for conductive additives such as carbon black which are often mixed in the cathode. Thus, the electrode binder bound to the surface of the cathode active material can interact with the conductive additive and physically bind the conductive additive, thereby producing a strong composite consisting of the cathode active material, the electrode binder and the conductive additive. Thus, a uniform distribution of the components in the cathode composite material is also obtained.
[0033] According to another aspect, the basic skeleton G is modified with at least one radical, heteroatom, side chain or functional group.
[0034] The group can be a linear, branched or cyclic C 1 -C 10 Perfluoroalkyl.
[0035] Terminology C 1 -C 10 Perfluoroalkyl within the meaning of the present invention includes linear, branched or branched saturated perfluorocarbon radicals having 1 to 10 carbon atoms.
[0036] Examples of suitable perfluoroalkyl groups are trifluoromethyl, perfluoroethyl, perfluoropropyl, perfluoroisopropyl, perfluoro-n-butyl, perfluoro-sec-butyl, perfluoroisobutyl and perfluoro-tert-butyl.
[0037] The heteroatom may be arranged in a bridging manner between two repeating units and connect them to one another, wherein the heteroatom is selected from elements of Group 15 and Group 16 of the Periodic Table of Elements.
[0038] For example, an oxygen atom or a nitrogen atom can be used as a heteroatom.
[0039] The side chains may be selected from acrylonitrile-butadiene rubber (HNBR), carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyacrylate (PAA), polyvinyl pyrrolidone (PVP), and polyvinyl alcohol (PVA).
[0040] The functional group may be selected from hydroxide, amine, carboxylic acid, ketone, anhydride (eg maleic anhydride) and sulfoxide groups.
[0041] The modification of the basic skeleton G with radicals, heteroatoms, side chains or functional groups described here serves primarily to increase the affinity of the electrode binder for the conductive additive. In addition, the electrochemical properties of the cathode formed thereby can also be adjusted.
[0042] According to another aspect of the invention, the electrode binder (B) is covalently bonded to the surface of the component (A) via anchoring groups. Anchoring groups are generally understood to be chemical groups which anchor, ie covalently bond, the electrode binder to the surface of the cathode active material.
[0043] As described above, at least a portion of the electrode binder of component (B) is covalently bonded to the surface of the cathode active material of component (A), wherein the electrode binder is covalently bonded to the surface via an anchoring group. The portion of the electrode binder of component (B) that is not bonded to the surface of the cathode active material particles may optionally have an anchoring group.
[0044] In principle, the anchoring group is not chemically restricted and any chemical group known in the art that is capable of covalently bonding the oxidized surface of the cathode active material to the electrode binder may be used.
[0045] Preferably, the anchoring group is selected from amide groups, amine groups, alkyne groups, alkene groups, hydroxide groups, carboxyl groups, ether groups, phosphonate groups, silane groups, silyl groups, siloxane groups, halosilane groups, carbamoyl groups, sulfonate groups, carboxylic acid anhydride groups and sulfonic acid amide groups.
[0046] According to another aspect of the present invention, the electrode binder (B) at least partially, preferably completely covers the surface of the particles of the cathode active material. If the electrode binder (B) completely covers the surface of the particles of the cathode active material, the electrode binder can also be understood as a coating that encapsulates the particles of the cathode active material (A).
[0047] In one variation, the average coverage of the particles of cathode active material is from 0.05 to 0.9 m 2 Surface area of cathode active material 0.005 to 0.1 g of electrode binder. Said range preferably applies to cathode active materials having a particle diameter in the micrometer range (≥1 μm), such as NCM or LCO.
[0048] In another embodiment, the average coverage of the particles of cathode active material is from 10 to 15 m 2 The surface area of the cathode active material is 0.05 to 1 g of electrode binder. The range preferably applies to particles with a diameter in the nanometer range and / or 10-15 m 2 / g of specific surface area of cathode active material, such as nano-LFP.
[0049] It is also conceivable that a mixture of a plurality of electrode binders each having anchoring groups different from one another is present on the particles of the cathode active material. Depending on the proportion of the electrode binders in the mixture, the electrochemical properties of the cathode obtained can thus be adjusted.
[0050] According to another aspect, the cathode further comprises at least one conductive additive (C) selected from the group consisting of conductive carbon black (carbon black), carbon nanotubes (CNTs), graphene, graphite, expanded graphite, carbon nanofibers, in particular vapor grown carbon nanofibers (VGCF), and combinations thereof.
[0051] Advantageously, the combination of a conductive additive (C) and an electrode binder (B) bonded to the surface of the cathode active material (A) enables the production of particularly efficient cathodes for lithium-ion batteries, since the conductive additive (C) used particularly increases the conductivity of the cathode. In addition, synergistic effects between electrode binder and conductive additive can be achieved, since the electrode binder (B) has a particular affinity for the conductive additive (C), which binds itself and brings it into the vicinity of the cathode active material (A), on the surface of which the electrode binder (B) binds itself.
[0052] In another aspect of the present invention, the cathode further comprises one or more additives (D). The one or more additives (D) are selected from the group consisting of bonding aids, fillers, dispersants and additional adhesion promoters such as acrylates or methacrylic acids.
[0053] Binding aids are understood below as compounds and substances that act in the same way as electrode binders (B), i.e., they have an affinity for the conductive additive and hold the constituent substances of the cathode together, but are not bound to the surface of the cathode active material. Alternatively, they are present in a substantially unbound manner in the composite material.
[0054] In another aspect, the cathode comprises the following components, each based on the total weight of the cathode:
[0055] (A) 80-99 wt %, preferably 90-98 wt %, of at least one cathode active material, wherein the cathode active material is selected from lithium cobalt oxide (LCO), lithium nickel oxide (LNO), lithium nickel cobalt aluminum oxide (NCA), lithium nickel manganese cobalt oxide (NMC), lithium-rich and manganese-rich lithium nickel manganese cobalt oxide or lithium nickel manganese oxide (LMR), lithium manganese oxide (LMO), lithium iron phosphate (LFP), lithium manganese iron phosphate (LMFP), spinel lithium nickel manganese oxide (LNMO), and derivatives and combinations thereof;
[0056] (B) 0.5-3 wt %, preferably 1-2 wt % of at least one electrode binder;
[0057] (C) 0.05-5 wt%, preferably 0.5-3 wt%, of at least one conductive additive, wherein the conductive additive is selected from conductive carbon black, carbon nanotubes (CNTs), graphene, graphite, expanded graphite and carbon nanofibers, in particular vapor grown carbon nanofibers (VGCF) and combinations thereof; and
[0058] (D) 0-10 wt %, preferably 0.1-1 wt %, of at least one additive selected from bonding aids, fillers, dispersants and adhesion promoters and combinations thereof,
[0059] The proportions of components (A) to (D) add up to 100%.
[0060] This cathode has particularly good electrode properties and cell properties.
[0061] Furthermore, the invention relates to a lithium-ion battery having a cathode as described above.
[0062] The invention is based on the basic idea that the components of the cathode are particularly uniformly mixed with one another, which is achieved in particular by covalent bonding of at least a portion of the electrode binder to the surface of the cathode active material. As a result, in particular, various drying phenomena during the production of the cathode or the lithium ion battery can be avoided, so that the lithium ion battery according to the invention has a particularly good high current carrying capacity and cycle stability.
[0063] In addition to the cathode as described above, the lithium-ion battery also includes an anode and an electrolyte composition in contact with the cathode and the anode.
[0064] The anode is in principle not restricted, and all anodes known from the prior art for lithium-ion batteries can be used.
[0065] Preferably, the anode has an anode active material. Specifically, the anode active material can be selected from carbonaceous materials, silicon, silizium-suboxid, silicon alloys, lithium, lithium alloys, aluminum alloys, indium, indium alloys, tin, tin alloys, cobalt alloys, niobium pentoxide, titanium dioxide, titanates such as lithium titanate (Li 4 Ti 5 O 12 ), tin dioxide and mixtures thereof.
[0066] Particularly preferably, the anode active material is selected from synthetic graphite, natural graphite, graphene, mesoporous carbon, doped carbon, hard carbon, soft carbon, fullerenes, silicon-carbon composites, silicon, surface-coated silicon, silicon oxide, silicon alloys, lithium, aluminum alloys, indium, tin alloys, cobalt alloys and mixtures thereof.
[0067] In addition to the anode active material, the anode may also have further components and additives, for example a foil support, an electrode-to-electrode binder and / or conductivity improvers, such as conductive carbon black, conductive graphite, so-called "carbon nanotubes" (CNTs), carbon fibers and / or graphene. As further components and additives, all customary compounds and materials known in the prior art can be used.
[0068] The electrolyte composition is likewise not limited.
[0069] For example, the electrolyte composition may have a dialkyl carbonate, in particular a dialkyl carbonate selected from diethyl carbonate (DEC), dimethyl carbonate (DMC) or ethyl methyl carbonate (EMC) and combinations thereof.
[0070] As a further component, the electrolyte composition preferably comprises at least one lithium salt, which is preferably selected from lithium hexafluorophosphate (LiPF 6 ), lithium bis(fluoromethanesulfonyl)imide (LiFSl) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSl) and combinations thereof. DETAILED DESCRIPTION
[0071] Example
[0072] Various exemplary compositions for the cathode are given below.
[0073] The compositions presented are exemplary only and should not be construed restrictively.
[0074] Example composition 1 :
[0075] Basic skeleton PVDF + anchoring group silane + cathode active material
[0076] LiNi 0.8 Co 0.1Mn 0.1 O 2 (NCM811)
[0077] Example composition 2 :
[0078] Basic skeleton poly (vinylidene fluoride-hexafluoropropylene) copolymer (PVDF-HFP + anchor group phosphonate + cathode material LiFePO 4
[0079] Preparation of surface-modified cathode active material particles :
[0080] The cathode active material of component (A) is commercially available. Preferably, the cathode active material is already used in the form of a powder having a corresponding particle size distribution.
[0081] The cathode active material and electrode binder of component (A) are then converted into surface-modified cathode active material particles by means of a chemical reaction. To this end, a method disclosed in a scientific article such as "Recent advances in chemical surface modification of metal oxide nanoparticles with silane coupling agents: A review" by F. Ahangaran et al. (published in "Advances in colloid and interface science", Vol. 286, No. 102298, December 2020) can be used.
[0082] Reaction Example 1 :
[0083] For example, a fluorinated polymer having a basic skeleton G and provided with silanol functional groups can be reacted with an oxidized surface of a cathode active material, wherein water dissociation occurs and surface-modified cathode active material particles are obtained. Anchoring groups in the form of silyl groups are formed by the reaction, which covalently bond the basic skeleton G of the fluorinated polymer to the surface of the cathode active material.
[0084] Reaction Example 2 :
[0085] However, in a variant, it is also possible to use a base skeleton G provided with silicon-halogen groups (X 3-Si-G) fluorinated polymer. The reaction with the oxidized surface (-OH) and the dissociation and removal of hydrogen chloride result in the generation of silyl anchor groups (O-Si-G), which covalently bond the basic skeleton G of the fluorinated polymer to the surface of the cathode active material. For example, refer to WO2005 / 061631A2.
[0086] Reaction Example 3 :
[0087] In another variant, a fluoropolymer having a basic skeleton G and having phosphonic acid can be reacted with the oxidized surface of the cathode active material. Phosphonate groups are then formed on the surface of the cathode active material as anchor groups, which covalently bond the oxidized surface of the cathode active material to G of the fluoropolymer.
[0088] Preparation of cathode slurry and cathode :
[0089] The preparation of cathode slurry and cathode is described in more detail below.
[0090] The methods given here for preparing the cathode slurry and the cathode are to be understood as purely exemplary. The cathode can be prepared in principle by various methods known from the prior art.
[0091] First, surface-modified cathode active material particles are prepared as described above.
[0092] Next, the surface modified cathode active material particles are weighed and suspended in a carrier solvent together with conductive carbon black and other additives. The carrier solvent can be, for example, N-methyl-2-pyrrolidone (NMP). However, other organic solvents, such as acetone, can also be used, but water-based solvents can also be used. Because the electrode binder is attached to the cathode active material, it is advantageous to eliminate the need to dissolve the electrode binder in the carrier solvent in advance.
[0093] The suspension is stirred until a uniform suspension exists. A uniform cathode coating composition (cathode slurry) is formed. The viscosity of the cathode coating composition is preferably adjusted to 5 to 20 Pa·s -1 , which is called the target viscosity. The viscosity can be adjusted by adding a carrier solvent or by evaporating the carrier solvent.
[0094] In the next step, the cathode coating composition is applied to the current collector using a doctor blade or a wide-slot nozzle. To prepare the cathode, the current collector usually consists of aluminum foil.
[0095] Finally, the current collector with the applied cathode coating composition is dried. During the drying process, the wet coating composition is converted into a dry composite material. After drying and calendering (pressing), the cathode of the present invention is obtained.
[0096] The cathode preferably has a 18 mg / cm 2 The unit area weight and 3.4g / cm 3 The electrode density.
[0097] The cathode prepared in this way has a uniform distribution of cathode active material, conductive additive and electrode binder and is therefore particularly suitable for incorporation into lithium-ion batteries.
Claims
1. A cathode for a lithium ion battery, wherein the cathode comprises the following components: (A) at least one cathode active material; and (B) at least one electrode binder; The cathode active material of component (A) is present in the form of particles, and at least a portion of the electrode binder of component (B) is covalently bonded to the surface of the particles.
2. The cathode for a lithium ion battery according to claim 1, characterized in that: The cathode active material is selected from lithium cobalt oxide (LCO), lithium nickel oxide (LNO), lithium nickel cobalt aluminum oxide (NCA), lithium nickel manganese cobalt oxide (NMC), lithium nickel manganese oxide (NMx), lithium-rich and manganese-rich lithium nickel manganese cobalt oxide or lithium nickel manganese oxide (LMR), lithium manganese oxide (LMO), lithium iron phosphate (LFP), lithium manganese iron phosphate (LMFP), spinel lithium nickel manganese oxide (LNMO) and their derivatives and combinations.
3. The cathode for a lithium ion battery according to claim 1 or 2, characterized in that: The electrode binder of component (B) is a fluorine-containing polymer having a basic skeleton G containing at least one repeating unit selected from vinylidene fluoride (-CH2CF2-), tetrafluoroethylene (-CF2-CF2-) and hexafluoropropylene (-CF2CF(CF3)-).
4. The cathode for a lithium ion battery according to claim 3, characterized in that: The basic skeleton G is modified by at least one group, heteroatom, side chain or functional group, The group is a straight-chain, branched or cyclic C1-C 10 a perfluoroalkyl group, preferably a perfluoroalkyl group selected from the group consisting of trifluoromethyl, perfluoroethyl, perfluoropropyl, perfluoroisopropyl, perfluoro-n-butyl, perfluoro-sec-butyl, perfluoroisobutyl and perfluoro-tert-butyl, wherein the heteroatom is arranged bridgingly between two repeating units and connects them to one another, and wherein the heteroatom is selected from elements of Groups 15 and 16 of the Periodic Table of the Elements, wherein the side chains are selected from acrylonitrile-butadiene rubber (HNBR), carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyacrylate (PAA), polyvinyl pyrrolidone and polyvinyl alcohol (PVA), And wherein the functional group is selected from hydroxide, amine, carboxylic acid, ketone, anhydride and sulfoxide groups.
5. A cathode for a lithium-ion battery according to any one of the preceding claims, characterized in that The electrode binder (B) is covalently bonded to the surface of the component (B) via an anchoring group.
6. The cathode for a lithium ion battery according to claim 5, characterized in that: The anchoring group is selected from amide groups, hydroxide groups, carboxyl groups, ether groups, phosphonate groups, silane groups, silyl groups, siloxane groups, halosilane groups, carbamoyl groups, sulfonate and sulfonic acid amide groups, carboxylic acid anhydride groups, amine groups, alkyne groups and alkene groups.
7. A cathode for a lithium-ion battery according to any one of the preceding claims, characterized in that The electrode binder (B) at least partially, preferably completely covers the surface of the particles of the cathode active material (A).
8. The cathode for a lithium ion battery according to claim 7, characterized in that: The cathode has at least one of the following characteristics: - The average coverage of the particles of cathode active material is from 0.05 to 0.9 m 2 Surface area 0.005 to 0.1 g of electrode binder or per 10 to 15 m 2 Electrode binder with a surface area of 0.05 to 1 g; - the particles have a particle size distribution with an average particle diameter in the range of 0.01 μm to 30 μm, preferably in the range of 50 nm to 1000 nm; - a mixture of a plurality of electrode binders having anchoring groups that are different from each other is present on the particles of the cathode active material; - the cathode further comprises at least one conductive additive (C), wherein the conductive additive is selected from conductive carbon black, carbon nanotubes (CNTs), graphene, graphite, expanded graphite and carbon nanofibers, in particular vapor grown carbon nanofibers (VGCF), and combinations thereof; and - The cathode further comprises one or more additives (D) selected from the group consisting of binding aids, fillers, dispersants and adhesion promoters.
9. A cathode for a lithium-ion battery according to any one of the preceding claims, characterized in that The cathode comprises the following components, each based on the total weight of the cathode: (A) 80-98 wt %, preferably 90-98 wt %, of at least one cathode active material, wherein the cathode active material is selected from lithium cobalt oxide (LCO), lithium nickel oxide (LNO), lithium nickel cobalt aluminum oxide (NCA), lithium nickel manganese cobalt oxide (NMC), lithium-rich and manganese-rich lithium nickel manganese cobalt oxide or lithium nickel manganese oxide (LMR), lithium manganese oxide (LMO), lithium iron phosphate (LFP), lithium manganese iron phosphate (LMFP), spinel lithium nickel manganese oxide (LNMO), and derivatives and combinations thereof; (B) 0.5-3 wt %, preferably 1-2 wt % of at least one electrode binder; (C) 0.05-5 wt%, preferably 0.5-3 wt%, of at least one conductive additive, wherein the conductive additive is selected from conductive carbon black, carbon nanotubes (CNTs), graphene, graphite, expanded graphite and carbon nanofibers, in particular vapor grown carbon nanofibers (VGCF), and combinations thereof; and (D) 0-10 wt %, preferably 0.1-1 wt %, of at least one additive selected from bonding aids, fillers, dispersants and adhesion promoters and combinations thereof, The proportions of components (A) to (D) add up to 100%.
10. A lithium ion battery having a cathode according to any one of the preceding claims.
Citation Information
Patent Citations
Vinylidene fluoride copolymers
EP2147029B1
Battery with a recyclable dry particle based electrode
US20130157141A1
Functionalisation of oxidic particle surfaces, particles thus obtained, and the use thereof
WO2005061631A2